Spotted rose snapper (Lutjanus guttatus) aquaculture research and development as socio-economic alternative for Costa Rican fishing communities - Herrera-Ulloa, Angel (2010)
The spotted rose snapper (Lutjanus guttatus) is one of the main target coastal species, but landings are decreasing in quantity and size. Reports include a mean capture size of 50 cm with gill nets and 38 cm with bottom long lines, but mean capture size has diminished to 43 cm with gill nets. This shows that the fishing effort on the population is excessive and requires protection management for sustainable exploitation.